2020
DOI: 10.1002/cam4.3133
|View full text |Cite
|
Sign up to set email alerts
|

Charactering tumor microenvironment reveals stromal‐related transcription factors promote tumor carcinogenesis in gastric cancer

Abstract: Transcription factors represent the crucial role of controlling gene transcription in cancer development and progression. However, their functions in gastric cancer have not been thoroughly characterized. For this study, we comprehensively evaluated the correlation between infiltration patterns of tumor microenvironment (TME) cells and TFs expression in the cohort of stomach adenocarcinoma (STAD) from TCGA database. We integrally explored differential expression panel and prognostic value of candidate TFs in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…A large number of studies have shown that speci c genes and transcription factors play an important role in the TME of GC [15,17]. In recent years, many drugs targeting various components of the TME have been approved for clinical use, including aromatase, vascular endothelial growth factor (VEGF) and immune checkpoint inhibitors (ICIs) [18].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that speci c genes and transcription factors play an important role in the TME of GC [15,17]. In recent years, many drugs targeting various components of the TME have been approved for clinical use, including aromatase, vascular endothelial growth factor (VEGF) and immune checkpoint inhibitors (ICIs) [18].…”
Section: Discussionmentioning
confidence: 99%
“…In general, tumor stroma and cancer cells should have at least four critical capabilities to advance tumor development and progression, including mobility, ECM degradability, survival in blood circulation, and the ability to adapt and develop in a new tissue environment [ 24 ]. To acquire those traits, cancer cells employ the transcriptional factors (TFs), regulatory factors in orchestrating gene expression during the course of cancer development [ 28 ]. Recent studies demonstrated the potential of TFs to induce TME remodeling as well as governing the proliferation and migration of cancer cells [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To acquire those traits, cancer cells employ the transcriptional factors (TFs), regulatory factors in orchestrating gene expression during the course of cancer development [ 28 ]. Recent studies demonstrated the potential of TFs to induce TME remodeling as well as governing the proliferation and migration of cancer cells [ 28 , 29 , 30 ]. To this end, the TME transmits the oncogenic signals to activate the TFs.…”
Section: Introductionmentioning
confidence: 99%
“…The TME is primarily composed of two cell types: stromal components, including broblasts, endothelial cells, and mesenchymal stromal cells, and tumour-in ltrating immune cells (TICs), such as macrophages and T cells, whose reaction is regarded as a protective response against tumours [9][10]. TMEs not only secrete many soluble molecules, such as cytokines, chemokines, growth factors, and antibodies but also contribute to the presence of hypoxia and acidity, which determine the behaviour of cancers, such as survival, growth, proliferation, and metastasis [11][12].…”
Section: Introductionmentioning
confidence: 99%